1987
DOI: 10.1007/bf00145066
|View full text |Cite
|
Sign up to set email alerts
|

Seroepidemiological study on sexually transmitted diseases and hepatitis B in African promiscuous heterosexuals in relation to HTLV-III infection

Abstract: A seroepidemiological study was performed on HTLV-III, T. pallidum, C. trachomatis and Hepatitis B virus (HBV), in Butare, Rwanda, among 33 female prostitutes, 25 male customers of prostitutes, and 60 male and female controls. As compared with female controls the prostitutes had a higher prevalence of antibodies to HTLV-III (29/33 versus 4/33, p less than 0.001), T. pallidum (TPHA: 27/33 versus 6/33, p less than 0.001; RPR: 19/33 versus 2/33, p less than 0.001; FTA-Abs: 27/33 versus 5/33, p less than 0.001) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

1988
1988
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 17 publications
(6 reference statements)
1
8
0
Order By: Relevance
“…For example, there may exist a causal relation between several STDs and HIV infection 74,75 , resulting from the mutual dependence of HIV and STDs on patterns of sexual activity or from the effect HIV may have on the clinical course of the STD. Likewise, the differing role of the prepuce as a risk factor, depending on the prevalence of circumcision in a region, suggests that the prepuce Van Howe.…”
Section: Discussionmentioning
confidence: 99%
“…For example, there may exist a causal relation between several STDs and HIV infection 74,75 , resulting from the mutual dependence of HIV and STDs on patterns of sexual activity or from the effect HIV may have on the clinical course of the STD. Likewise, the differing role of the prepuce as a risk factor, depending on the prevalence of circumcision in a region, suggests that the prepuce Van Howe.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, HBV-positivity may reach as much as 80% in early childhood in endemic areas (8,17). Such data could explain why in some studies no correlations have been observed (13), whereas they have been reported in others (5,20). If this view holds true, HBV-positivity would be a better marker of high sexual activity than positivity for other STDs.…”
Section: Injections~blood Transfusionsmentioning
confidence: 46%
“…Former studies have reported a correlation between serological markers for syphilis and HIV (5,16,20), though others have denied it (13). Apparently an overall correlation does exist, at least for women, and is also observed in univariate analysis.…”
Section: Injections~blood Transfusionsmentioning
confidence: 97%
“…The strong association between past or present STDs and infection with HIV in prostitutes and their clients has been emphasised by epidemiological studies performed in eastern and central Africa. 16 17 Thus both laboratory and epidemiological studies support STDs as an enhancing factor in the heterosexual transmission of HIV. This could partly explain the relative lack of sexual transmission reported in the United States of America and Australia in non-promiscuous people.…”
Section: Discussionmentioning
confidence: 98%
“…We studied 17 consecutive African women seropositive for HIV (by an immunoenzyme test) who attended the department of gynaecology of the Centre Hospitalier de Kigali, Kigali, Rwanda, because they had leucorrhoea. They were compared with 17 consecutive seronegative patients of the same geographic origin attending the same department for the same reason.…”
Section: Patients and Serological Methodsmentioning
confidence: 99%